Key factors influencing smallholder market participation in the former homelands of South Africa : case study of the Eastern Cape - Hlomendlini, Pilile Hamlet (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2015.